Rekonsepsi Definisi dan Teori Intelijen dalam Keamanan Nasional - Riyanta, Stanislaus (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2025)
Intelligence plays a crucial role in maintaining a nation's national security, functioning not only as a tool for information gathering but also as a means of analyzing and interpreting data to support strategic decision-making. In the context of globalization and advancements in information technology, threats to national security have become increasingly complex, encompassing terrorism, cybercrime, and interstate conflicts. The reconceptualization of intelligence definitions and theories is essential to address modern challenges that are multidimensional in nature. This paper discusses various definitions of intelligence from experts, including the views of Sherman Kent, T.F. Troy, and D. Kahn, while emphasizing the importance of the processes of gathering, analyzing, and presenting relevant information. Furthermore, this paper highlights the need for integrating perspectives from both academics and practitioners to create a more holistic and adaptive understanding of intelligence. With a more inclusive approach, it is hoped that the intelligence strategies adopted by nations can remain relevant and effective in facing the continuously evolving challenges in the modern world.